2022
DOI: 10.3390/molecules27030816
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Molecular Docking Study of Novel 3-Phenyl-β-Alanine-Based Oxadiazole Analogues as Potent Carbonic Anhydrase II Inhibitors

Abstract: Carbonic anhydrase-II (CA-II) is strongly related with gastric, glaucoma, tumors, malignant brain, renal and pancreatic carcinomas and is mainly involved in the regulation of the bicarbonate concentration in the eyes. With an aim to develop novel heterocyclic hybrids as potent enzyme inhibitors, we synthesized a series of twelve novel 3-phenyl-β-alanine 1,3,4-oxadiazole hybrids (4a–l), characterized by 1H- and 13C-NMR with the support of HRESIMS, and evaluated for their inhibitory activity against CA-II. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Askin et al designed a protocol to synthesize new imidazole [2,1b] [1,3,4]thiadiazoles (73)(74)(75)(76)(77)(78)(79)(80)(81). Initially substituted benzyl chloride derivatives (62)(63)(64) were refluxed with KOH in presence of ethanol for 4-6 h to obtain 2-amino-1,3,4-thiadiazoles (66)(67)(68) Newly synthesized compounds were tested for their inhibitory activity against hCA I and hCA II by taking standard AAZ and THA and it was observed that compound 70b and 71 were found to be most potent against hCA I with K i values of 23.44 ± 4.92 and 51.53 ± 10.74 nM, respectively.…”
Section: S C H E M E 7 Synthesis Of 42(a-l)mentioning
confidence: 99%
See 2 more Smart Citations
“…Askin et al designed a protocol to synthesize new imidazole [2,1b] [1,3,4]thiadiazoles (73)(74)(75)(76)(77)(78)(79)(80)(81). Initially substituted benzyl chloride derivatives (62)(63)(64) were refluxed with KOH in presence of ethanol for 4-6 h to obtain 2-amino-1,3,4-thiadiazoles (66)(67)(68) Newly synthesized compounds were tested for their inhibitory activity against hCA I and hCA II by taking standard AAZ and THA and it was observed that compound 70b and 71 were found to be most potent against hCA I with K i values of 23.44 ± 4.92 and 51.53 ± 10.74 nM, respectively.…”
Section: S C H E M E 7 Synthesis Of 42(a-l)mentioning
confidence: 99%
“…Newly synthesized compounds were screened for inhibitory activity against hCA II using colorimetric method by taking AAZ as standard drug and it was observed that all these derivatives except 412d (R = 4- Newly synthesized compounds were also subjected to molecular docking studies to determine binding affinity of compounds and it was observed that active compounds fitted perfectly in active site of CA II and formed hydrogen bond with Thr199, Thr200, Gln92 of CA II [75] (Scheme 56). All synthesized compounds were tested for in vitro inhibitory activity against hCA I, II, IX, and XII by taking AAZ as standard drug and it was observed that quinazoline compounds 414 (R = OCH 2 CH 3 ),…”
Section: S C H E M E 52 Synthesis Of 387(a-u)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the selected compounds from the literature are reported here in Figure as hCA II and β-glucuronidase inhibitors, which are rationalized with current work to disclose their metabolic liabilities and/or biological potencies.…”
Section: Introductionmentioning
confidence: 99%
“…The structures were fully established through various spectroscopic methods. The carbonic anhydrase inhibitory profile was examined and the acquired in vitro efficacy was remarkable, which was further validated with computational modeling analysis [ 11 ].…”
mentioning
confidence: 99%